2021
DOI: 10.3390/cancers13112575
|View full text |Cite
|
Sign up to set email alerts
|

Challenging, Accurate and Feasible: CAF-1 as a Tumour Proliferation Marker of Diagnostic and Prognostic Value

Abstract: The discovery of novel biomarkers of diagnostic, prognostic, and therapeutic value is a major challenge of current cancer research. The assessment of tumour cell proliferative capacity is pivotal for grading and clinical decision-making, highlighting the importance of proliferation markers as diagnostic and prognostic tools. Currently, the immunohistochemical analysis of Ki-67 expression levels is routinely used in clinical settings to assess tumour proliferation. Inasmuch as the function of Ki-67 is not fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 75 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…CAF-1 functions as a histone chaperone that assembles newly synthesized histone H3/H4 onto replicating DNA [ 112 ]. Therefore, CAF-1 is essential for DNA replication during the process of nucleosome formation, as well as chromatin recovery after DNA repair [ 113 ].…”
Section: Histone Chaperones In Digestive Cancersmentioning
confidence: 99%
“…CAF-1 functions as a histone chaperone that assembles newly synthesized histone H3/H4 onto replicating DNA [ 112 ]. Therefore, CAF-1 is essential for DNA replication during the process of nucleosome formation, as well as chromatin recovery after DNA repair [ 113 ].…”
Section: Histone Chaperones In Digestive Cancersmentioning
confidence: 99%
“…CAF-1, an outstanding marker of proliferating cell ( Polo et al, 2004 ), has been found to be the key regulator in DNA replication and chromatin restoration ( Zheng et al, 2018 ). The expression of CAF-1 is positively correlated with the expression of Ki-67 in cancers ( Sykaras et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…CAF-1, an outstanding marker of proliferating cell [3], has been found to be the key regulator in DNA replication and chromatin restoration [4]. The expression of CAF-1 is positively correlated with the expression of Ki-67 in cancers [5].…”
Section: Introductionmentioning
confidence: 99%
“…CAF-1 is a nuclear complex containing three subunits in human cells, CHAF1A (p150), CHAF1B (p60), and RBBP4 (p48) [5]. Among the three subunits, CHAF1A is the major one and plays essential role in CAF-1 complex [6,7].…”
Section: Introductionmentioning
confidence: 99%